2014
DOI: 10.1186/1471-2148-14-148
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescent sperm in a transparent worm: validation of a GFP marker to study sexual selection

Abstract: BackgroundSexual selection has initially been thought to occur exclusively at the precopulatory stage in terms of contests among males and female mate choice, but research over the last four decades revealed that it often continues after copulation through sperm competition and cryptic female choice. However, studying these postcopulatory processes remains challenging because they occur internally and therefore are often difficult to observe. In the transparent free-living flatworm Macrostomum lignano, a recen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
84
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 50 publications
(87 citation statements)
references
References 51 publications
3
84
0
Order By: Relevance
“…The free‐living flatworm Macrostomum lignano Ladurner, Schärer, Salvenmoser, Rieger 2005 (Rhabditophora, Macrostomorpha) has emerged as a model for a broad range of research topics (Ladurner, Schärer, Salvenmoser, & Rieger, ), including the biology of aging (Mouton, Grudniewska, Glazenburg, Guryev, & Berezikov, ; Mouton et al, ), bioadhesion (Lengerer, Hennebert, Flammang, Salvenmoser, & Ladurner, ; Lengerer et al, ; Wunderer et al, ), regeneration (Egger, Ladurner, Nimeth, Gschwentner, & Rieger, ; Lengerer et al, ), stem cell biology (Grudniewska et al, ; Ladurner et al, ), and sexual selection (Marie‐Orleach, Janicke, Vizoso, David, & Schärer, ; Schärer, Littlewood, Waeschenbach, Yoshida, & Vizoso, ; Sekii et al, ). This research has led to the establishment of many resources and tools that are crucial for a modern genetic and genomic model, including in situ hybridization (Pfister et al, ), RNA interference (Kuales et al, ; Sekii et al, ), gene expression (Arbore et al, ; Grudniewska et al, ; Lengerer et al, ), genome and transcriptome assemblies (Wasik et al, ; Wudarski et al, ), transgenesis (Marie‐Orleach, Janicke, Vizoso, Eichmann, & Schärer, ; Wudarski et al, ), and a clarification of the phylogenetic context (Janssen et al, ; Schärer et al, ). Jointly, these achievements make M. lignano an excellent model to complement the, in several aspects, more established planarian flatworm models (Newmark & Sánchez Alvarado, ; Pellettieri & Sánchez Alvarado, ; Rink, ; Rouhana et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The free‐living flatworm Macrostomum lignano Ladurner, Schärer, Salvenmoser, Rieger 2005 (Rhabditophora, Macrostomorpha) has emerged as a model for a broad range of research topics (Ladurner, Schärer, Salvenmoser, & Rieger, ), including the biology of aging (Mouton, Grudniewska, Glazenburg, Guryev, & Berezikov, ; Mouton et al, ), bioadhesion (Lengerer, Hennebert, Flammang, Salvenmoser, & Ladurner, ; Lengerer et al, ; Wunderer et al, ), regeneration (Egger, Ladurner, Nimeth, Gschwentner, & Rieger, ; Lengerer et al, ), stem cell biology (Grudniewska et al, ; Ladurner et al, ), and sexual selection (Marie‐Orleach, Janicke, Vizoso, David, & Schärer, ; Schärer, Littlewood, Waeschenbach, Yoshida, & Vizoso, ; Sekii et al, ). This research has led to the establishment of many resources and tools that are crucial for a modern genetic and genomic model, including in situ hybridization (Pfister et al, ), RNA interference (Kuales et al, ; Sekii et al, ), gene expression (Arbore et al, ; Grudniewska et al, ; Lengerer et al, ), genome and transcriptome assemblies (Wasik et al, ; Wudarski et al, ), transgenesis (Marie‐Orleach, Janicke, Vizoso, Eichmann, & Schärer, ; Wudarski et al, ), and a clarification of the phylogenetic context (Janssen et al, ; Schärer et al, ). Jointly, these achievements make M. lignano an excellent model to complement the, in several aspects, more established planarian flatworm models (Newmark & Sánchez Alvarado, ; Pellettieri & Sánchez Alvarado, ; Rink, ; Rouhana et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Several techniques are developed for Macrostomum , including antibody labeling, in situ hybridization (ISH), RNA interference (RNAi), and gene expression analysis (Ladurner et al, 2000, 2005; Pfister et al, 2007; De Mulder et al, 2009; Arbore et al, 2015; Plusquin et al, 2016). Recently, the first genome and transcriptome assemblies were published (Wasik et al, 2015), and transgenesis utility was demonstrated (Marie-Orleach et al, 2014, 2016). Despite this available toolbox, the described molecular markers for proliferating cells in M. lignano are still limited to piwi and vasa , which are expressed in both somatic neoblasts and proliferating germline cells (Pfister et al, 2007, 2008; De Mulder et al, 2009; Zhou et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Given its promise as a model for studying mechanisms governing pluripotency, a number of groups have worked to establish M. lignano as a model to study stem cell biology and regeneration (16,19,20), sexual selection and reproductive biology (21,22), bioadhesion (23), and neurobiology (24). Efforts of the M. lignano community have resulted in the development of a number of tools that can be used to study M. lignano biology (15,21,(25)(26)(27).…”
mentioning
confidence: 99%
“…Efforts of the M. lignano community have resulted in the development of a number of tools that can be used to study M. lignano biology (15,21,(25)(26)(27).…”
mentioning
confidence: 99%